Purification and characterisation of an inhibitor of rubber biosynthesis from C-serum of Hevea brasiliensis latex - Yusof Faridah; Walker John M; Ward Malcolm A (Journal of Rubber Research, 1998)
A preeinaceous inhibitor of rubber biosynthesis was purified from the C-serum of Hevea brasiliensis latex. The protein inhibited the incorporation of isopentenyl diphosphate into rubber. Purification was achieved by employing three column chromatography meethods Sephadex G-150 gel-filtration, DEAE-Cellulose ion exchangd gchromatography and Phenyl Sepharose CL-4B hydrophobic interaction chromatography. The inhibitor makes up 0.3;ofthe total protein in the C-serum solids and was shown to have a molecular weight of 43 700 Da by mass spectrometry. The protein was blocked at the N-terminal. Amino acid sequence of petpide fragments obtained from CNBr, endoproteinase Lysine-C and trypsin digestions shwoed this protein to have regions of sequence similar to patatin, a protein that constitutes approximately 40;of the total protein present in mature potato tubers (Solanum tuberosum). Investigations showed that, like patatin, the inhibitor has liplytic acyl hydrolase (LAH) activity. Based on these observations, it is thought that the inhibitory effect is due to the destruction by LAH of the integrity of the rubber particle membrane in which the biosynthetic enzymes are thought to be embedded.